Review on the Durability of Polypropylene Fibre-Reinforced Concrete - Yanzhu Liu; Liang Wang; Ke Cao; Lei Sun (Advances in Civil Engineering)
Polypropylene fibre (PPF) is a kind of polymer material with light weight, high strength, and corrosion resistance. The crack resistance of concrete can be improved by adding PPFs. PPF can optimize the pore size distribution of concrete. As a result, the durability of concrete is significantly enhanced since PPF can block the penetration of water or harmful ions in concrete. This paper summarizes the influence of polypropylene fibre on the durability of concrete, including drying shrinkage, creep, water absorption, permeability resistance, chloride ion penetration resistance, sulfate corrosion resistance, freeze-thaw cycle resistance, carbonation resistance, and fire resistance. The authors analysed the effects of fibre content, fibre diameter, and fibre hybrid ratio on these durability indexes. The durability property of concrete can be further improved by combining PPFs and steel fibres. The drawbacks of PPF in application in concrete are the imperfect dispersion in concrete and weak bonding with cement matrix. The methods to overcome these drawbacks are to use fibre modified with nanoactive powder or chemical treatment. At last, the authors give the future research prospects of concrete made with PPFs.